Pharmacokinetics of TKM-130803 in Sierra Leonean patients with Ebola virus disease: Plasma concentrations exceed target levels, with drug accumulation in the most severe patients - Scott, JT; Sharma, R; Meredith, LW; Dunning, J; Moore, CE; Sahr, F; Ward, S; Goodfellow, I; Horby, P (Elsevier, 2020)
Background: TKM-130803 is a specific anti-EBOV therapeutic comprised of two small interfering RNAs (siRNA) siLpol-2 and siVP35-2. The pharmacokinetics (PK) of these siRNAs was defined in Ebola virus disease (EVD) patients, with reference to efficacy (ET) and toxicology thresholds (TT). The relationship between PK and patient survival was explored.